Two‐Photon Laser Writing of Soft Responsive Polymers via Temperature‐Controlled Polymerization. Issue 8 (26th June 2021) - De Bellis, Isabella; Nocentini, Sara; Delli Santi, M. Giulia; Martella, Daniele; Parmeggiani, Camilla; Zanotto, Simone; Wiersma, Diederik S.
Abstract: Enhancing the resolution of 3D patterning techniques in functional soft polymers enlarges the application areas of responsive shape‐changing materials, for tunable nanophotonics and nanorobotics. Thanks to the recent advances of polymer science, the palette of available materials for nanomanufacturing is becoming wider and wider—although the comprehension of their polymerization process by two‐photon polymerization is still incomplete. In this work, both shrinking of the minimal polymerizable unit and a significant improvement of the mechanical stability of microstructured soft polymers, in particular of liquid crystalline networks, are demonstrated. To this aim, temperature control enhances the resolution and reduces the swelling of the polymerized structures, thus avoiding deviations of the final structure from the intended design. This fine control on the nanoscale features enables the use of soft responsive materials not only for bulky microelements, but also for high‐resolution structures with more complex design. Abstract : Direct laser writing with increased resolution, never reached for liquid crystalline networks, is demonstrated at controlled polymerization temperatures. A careful voxel shape analysis demonstrates that temperature, swelling, and molecular anisotropy rule the 3D polymerizable unit dimension. The resulting voxel, now comparable with the typical one of commercial resists, enlarges the application field of responsive polymers without degradation of the structure rigidity.